PROBLEMS OF TRANSLATING PHILOSOPHICAL TERMS - Shananova Laylo (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article considers translation as a dialectical unity of linguistic and philosophical approaches, achievable within the boundaries of the “translatological triangle”: the original text and the translated text are always mediated by the translator’s personality. Translation transformation as a hermeneutic experience is the essence of overcoming the conflict between the idiomatic nature of philosophical concepts and their semantic variability.